Cryptanalysis of two similar chaos-based image encryption schemes. Issue 6 (2nd November 2021) - Mastan, J. Mohamedmoideen Kader; Pandian, R.
Abstract: Chaos based image encryption cryptosystems have garnered much attraction in the recent past. In this regard, recently, two chaos-based image encryption algorithms have been proposed. Both the cryptosystems exhibit very good cryptographic metrics. The first cryptosystem utilizes cryptographic tweaks and other cryptographic primitives to encrypt digital images. This cryptosystem also relies on the idea that a tweak can make the cryptosystem secure. Our paper points out that merely using a tweak doesn't make the cryptosystem secure and additionally, the structure and stages in the algorithm bear inability to preserve confidentiality of sensitive data. The second cryptosystem is an enhancement of another cryptosystem. Our work indicates that the enhancement in the second cryptosystem is also weak and allows an adversary to retrieve the exact key itself. Both the cryptosystems have similar weaknesses and don't follow the guidelines laid down by National Institute of Standards and Technology (NIST). It is observed that both the cryptosystems can be broken, to reveal the exact chaotic sequence used for encryption, using a Chosen Plaintext Attack. From this work, it is realized that the weaknesses in the methods can be partially avoided by strictly following the rules laid down by the cryptographic community and NIST. Apart from this, it is expected that future cryptosystems follow all the suggestions mentioned in our work so that, before the cryptosystem is out for attack by cryptanalysts, it is scrutinized sufficiently.